The Role of Mindfulness and Patience on Social Anxiety in Using Social Media in Emerging Adulthood - Aryandari, Diandra; Nashori, Fuad (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Individuals in emerging adulthood are prone to experience social anxiety, especially in social media, as they are prone to receive responses, criticism, or judgment from others or themselves when sharing content related to themselves. This study aims to determine the relationship between mindfulness and patience with social anxiety in social media in emerging adulthood. This study used a quantitative approach, namely multivariable correlation with the relationship model of three variables analyzed using regression analysis. 542 participants in emerging adulthood who are active social media users were involved in this study. Data were collected using the Social Anxiety Scales for Social Media Users (SAS-SMU), Mindful Attention Awareness Scale (MAAS), and the Patience Scale. The results of the study showed that mindfulness and patience had a significant effect on social anxiety in social media. Besides, each independent variable significantly reduces social anxiety in social media. Then, mindfulness plays a stronger role in overcoming social anxiety in social media. The implications of this research show that mindfulness and patience can reduce social anxiety on social media. It is necessary to apply mindfulness in daily life to reduce social anxiety in social media in emerging adulthood.